IMPLEMENTASI PERSAMAAN MOORE AND BURCH UNTUK MENENTUKAN INDEKS EROSI POTENSIAL PADA DAERAH ALIRAN SUNGAI (DAS) BABAKAN KABUPATEN BREBES JAWA TENGAH - Poegoeh Prasetyo Rahardjo; Alexander Tunggul Sutan Haji (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
The research aim to make an spatial information system to determine Potential Erosion Index in Babakan watershed area to learning, testing, and evaluating erosion level using Geographical Information System (GIS). Spatial analysis that used are Digital Terrain Modelling (DTM)/Digital Elevation Modelling (DEM) that integrated with Moore and Burc (1986) equations. This analyze represented land surface relief in 3 dimension form to increase correctness of identification of land slope, catchment area, flow direction, flow accumulation, length of flow, and flowing area. The datas that used on this research are digital tophographic map 1:25000 scale, watershed boundary map, rivers network of Babakan watershed map, and landuse map. Analysis on this research is DEM processing from the countour map than integrated them to the Moore and Burch (1986) equations. The result of this research shown that minimum Potential Erosion Index value is 0 and maximum is 12244515840.